Terrorism in perspective - Mahan, Sue (Sage Publications, 2013)
This book takes a broad-based approach that emphasizes the historical, cultural, political, religious, social, and economic factors that underlie an understanding of both global and domestic terrorism. This unique text-reader combines original essays with the best of the existing literature on terrorism. Each chapter of this text begins with an overview essay written by the authors, followed by two relevant and engaging articles culled from a wide variety of popular, academic, and governmental sources. This is the only major terrorism text to incorporate readings from top terrorism experts into a traditional textbook format, allowing readers to deepen their understanding of each aspect of terrorism.